Perbandingan Hukum Persaingan Usaha Terkait Pembuktian Tindakan Diskriminasi di Sektor Digital - Rezaldy; Nanda Diyan Saputra (Jurnal Persaingan Usaha, 2023)
The development of the digital economy in Indonesia makes it easy for business actors to run their business, besides that it also has the potential to cause violations in the business competition sector such as the act of blocking internet access carried out by PT Telkom Indonesia against NETFLIX, this of course creates competition related to the verification mechanism. The purpose of this study is to find out the concept of regulation and proof in warning actions in the digital sector between Indonesia and Singapore. The theory used in analyzing the problems in this paper is the rule of reason and legal certainty. The conclusions obtained in this study are the provisions of Article 19 letter (d) of Law no. 5 of 1995 jo Perkom KPPU No.3 of 2011 has not comprehensively regulated complaints regarding actions in the digital sector, causing difficulties in the verification process, for this reason the authors compared it with the regulation prohibiting warning actions in the digital sector in Singapore.